Hubungan Tingkat Literasi Kesehatan dengan Penerapan Pola Hidup Sehat pada Petani di Kelurahan Tenggarang Kabupaten Bondowoso: The Relationship between Health Literacy Levels and Lifestyle Implementation Healthy for Farmers in Tenggarang Village, Bondowoso Regency - Lulu Dewanti; Anisah Ardiana; Kholid Rosyidi Muhammad Nur; Dodi Wijaya; Alfid Tri Afandi (Fakultas Keperawatan Universitas Andalas, 2023)
Encouraging a healthy lifestyle is important for farmers, as it significantly influences their long-term well-being. Unfortunately, a considerable number of farmers engage in risky health practices, primarily due to their limited health literacy. This research delves into the intricate connection between health literacy and the adoption of a healthy lifestyle among farmers residing in Tenggarang Urban Village, Bondowoso Regency. Our study employed a cross-sectional design, encompassing a sample of 90 farmers chosen through cluster random sampling. To assess health literacy, we employed the Health Literacy Short-Form Survey Questionnaire (HLS-EU-SQ10-IDN), designed for use in Indonesia. Additionally, we measured the extent of a healthy lifestyle using the Health Promoting Lifestyle Profile II (HPLP-II). For statistical analysis, we utilized Kendall’s Tau-b correlation test, with a significance level set at α < 0.05. Our findings unveiled that an impressive 78.9% of respondents exhibited commendable health literacy levels, with 60% demonstrating a strong dedication to leading a healthy lifestyle. Crucially, we identified a statistically significant and positive correlation between health literacy and the adoption of a healthy lifestyle among farmers (p value = 0.000 and r = 0.393). To further enrich this area of study, future research could delve deeper into the factors that influence health literacy and the facilitators encouraging the adoption of healthy lifestyle practices among farmers. Consequently, stakeholders are encouraged to formulate educational strategies aimed at bolstering health literacy within the farming community, coupled with a comprehensive understanding of the factors influencing the adoption of healthy lifestyles to effectively enhance farmer well-being.